897 PEAK RIGHT ATRIAL LONGITUDINAL STRAIN: A NEW PARAMETER IN PREDICTING VENOUS CONGESTION. (15th December 2022) - Niro, Lorenzo; Iseppi, Manuela; Fanti, Diego; Maffeis, Caterina; Bergamini, Corinna; Rossi, Andrea; Tafciu, Elvin; Benfari, Giovanni; Luciano Ribichini, Flavio
Abstract: Background: tricuspid regurgitation (TR) of either organic or functional etiology can lead to systemic venous congestion particularly in its more severe forms. Little is known about the role of the right atrium (RA) which acts as an intermediate player between TR and systemic veins. Purpose: to assess the influence of right atrial size and function on venous congestion in TR patients. Methods: 101 stable patients with at least mild to moderate TR were enrolled at the time of echocardiography (age 74±13 years, 37% male). Systemic congestion was assessed by inferior vena cava (IVC) diameter and right atrial pressure (RAP) estimated according to inferior vena cava diameter and collapsibility. TR severity was quantified by means of proximal isovelocity surface area (PISA) derived effective regurgitant orifice area (EROA) and regurgitant volume (RVol). RA and right ventricular (RV) function were assessed respectively by peak atrial longitudinal strain (PALS) and free wall longitudinal strain (FWLS) while indexed RA volume (RAVi) by Simpson's disk summation method. Results: TR was quantified mild or moderate in 52 patients and more than moderate in 49 patients (mean EROA 37±31 mm2; mean RVol 34±23 ml). Mean indexed RA volume was 58±31 ml/m2; mean RA strain was 18±11% and mean RV strain (free wall) was -21 ± 7%. Mean IVC diameter was 20±6 mm; estimated RAP was ≤5 mmHg in 32 patients, 6-10 mmHg in 26, 11-15 mmHg in 26 and greater than 15 mmHg in 17 patients. In univariate analysis both IVC diameter and RAP correlated significantly with EROA, RVol, RAVi and RA strain (p<0.0001 for all); only RAP correlated with RV strain. In linear multivariate analysis only RAVi and RA strain were independent predictors of IVC diameter (p=0.01 and <0.0001, respectively), and only RVol and RA strain were independent predictors of RAP (p=0.001 and 0.002, respectively). We found a RA strain cut-off of -15% to have a sensitivity of 82% and specificity of 70% to identify a RAP greater than 15 mmHg (area under the curve-AUC 0.842). Conclusions: RA size and function together with the TR-related volume overload were independent predictors of venous congestion. Among these variables, only RA strain predicted both parameters of venous congestion.